Multifaceted roles of WRKY transcription factors in abiotic stress and flavonoid biosynthesis - Zhang, Jinnan; Zhao, Haiqing; Chen, Lu; Lin, Jiacheng; Wang, Zhile; Pan, Jiaqi; Yang, Fan; Ni, Xiaoli; Wang, Yiang; Wang, Yuhua; Li, Rui; Pi, Erxu; et al. (Frontiers in Plant Science, 2023)
Increasing biotic and abiotic stresses are seriously impeding the growth and yield of staple crops and threatening global food security. As one of the largest classes of regulators in vascular plants, WRKY transcription factors play critical roles governing flavonoid biosynthesis during stress responses. By binding major W-box cis-elements (TGACCA/T) in target promoters, WRKYs modulate diverse signaling pathways. In this review, we optimized existing WRKY phylogenetic trees by incorporating additional plant species with WRKY proteins implicated in stress tolerance and flavonoid regulation. Based on the improved frameworks and documented results, we aim to deduce unifying themes of distinct WRKY subfamilies governing specific stress responses and flavonoid metabolism. These analyses will generate experimentally testable hypotheses regarding the putative functions of uncharacterized WRKY homologs in tuning flavonoid accumulation to enhance stress resilience.